Incidence of Maize Weevil (Sitophilus zeamais Motsch) and its Association with Green Fungus (Aspergillus flavus Link) in Maize Under Storage at Chitwan and Surkhet Districts of Nepal - Bhusal, K.; Khanal, D. (Journal of the Institute of Agriculture and Animal Science, 2018)
A survey of maize-growing areas of Surkhet and Chitwan, Nepal (April to May 2017) was conducted to know about the incidence, relationship and loss in stored maize due to Maize weevil (Sitophilus zeamais Motsch) and (Aspergillus flavus Link). Sixty households from each district were surveyed and the data was analyzed using SPSS and Microsoft Excel. Result revealed that there is severe infestation of maize weevil and green fungus in stored maize. 97.5% of stored samples had incidence of Aspergillus, whereas 96.7 % samples had maize weevils. 15.7% of the farmers apply sun drying and removal of the A. falvus infested seed while remaining 84.3% of the farmers use no any measure of control. Results from Chi- Square test indicated significant relation (χ2 = 122.10, P<0.01) between incidence of weevil infestation and occurrence of green fungus in the study area. The Phi coefficient value (1.00) shows the perfect relationship exist between weevil and green fungus occurrence in the study areas. The overall annual damage by the A. flavus was 6.39%. Therefore, it can be said that maize weevil is the major insect while A. flavus is major pathogen of maize grains at storage. The relationship between the occurrences of both pests was highly significant which indicated the positive relationship, i.e. the weevil plays an essential role in growth and spread of fungus.